1990
DOI: 10.1080/00325481.1990.11704633
|View full text |Cite
|
Sign up to set email alerts
|

Drug allergy

Abstract: The problems in identifying and managing drug allergy are myriad, primarily because of the number of possible agents involved, the lack of objective diagnostic methods, and the varied signs and symptoms that may occur. Allergic reactions can be life-threatening and are avoidable in most cases. A careful and serious approach is important because the effect of medical decisions can be significant. Physicians should keep in mind that an allergic reaction to any drug can occur in any patient at any time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The reported cross-reactivity with cephalosporin in patients allergic to penicillin is approximately 10% [34-37]. A large study by Atanasković-Marković et al [5] reported that cross-reactivity depends on the generation of cephalosporins and varies between 0.3% (ceftriaxone) and 23.9% (cephalexin).…”
Section: Discussionmentioning
confidence: 99%
“…The reported cross-reactivity with cephalosporin in patients allergic to penicillin is approximately 10% [34-37]. A large study by Atanasković-Marković et al [5] reported that cross-reactivity depends on the generation of cephalosporins and varies between 0.3% (ceftriaxone) and 23.9% (cephalexin).…”
Section: Discussionmentioning
confidence: 99%